Emergence of Classicality from Initial Quantum World for Dissipative Optical Waves - J. R. Choi (Advanced Electromagnetics, 2016)
For light waves propagating in dissipative media, the emergence of classical characteristics from the initial quantum world is investigated. Two classicality measures of the system, which are the measure of the degree of (relative) classical correlation and that of the degree of quantum decoherence are analyzed.